Evaluation of Euphorbia poissonii pax for the formulation of an -incapacitating agent - Awe, F.E.; Adeyemi, M.M.; Yakassai, J.B.; Kolawale, E.A. (Scientia Africana, 2023)
This research was designed to explore the biological effects of compounds isolated from Euphorbia poissoni pax for the formulation of an Incapacitating Agent against Albino rat; which will serve as an indigenous weapon for the Nigerian defence system and also as an insecticide. Chloroform extracts of Euphorbia poissoni pax was subjected to preliminary phytochemical screening to ascertain the presence of phenolic compounds, alkaloids, saponins, and terpenoids. Fourier- Transform Infrared (FT-IR) spectroscopy and Gas Chromatography-Mass Spectrometry (GC-MS) analysis indicated the presences of some chemical compounds including (4-(4-Hydroxyphenyl)-4- methyl-2-pentanone) trimethylsilyl Ether, n-Hexadecanoic acid, Carbonic acid(1R)-(-)-menthylnonyl ester, 13-Octadecenoic acid methyl ester, 1,3,5-triazine, 2-chloro-4,6-bis(mthylthio) and Phthalic acid, 6-ethyloct-3-yl-2-ethylhexyl ester. In the chloroform extract. The LD50 of the plant extract was calculated to be 1733.33 mg/kg, which is within the OECD (Organization of Economic Cooperation and Development) guidelines. The extract exerted a potent biological activity at 1000 mg/kg on applying under pressure on the rat skin and incapacitated the rat for 2 minutes. The extract showed an effective insecticidal effect against cockroaches and beans weevils.